2021
DOI: 10.1038/s41598-021-90900-5
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choriocapillaris perfusion are associated with ankle-brachial-pressure-index and Fontaine stage in peripheral arterial disease

Abstract: The purpose of this prospective case–control study was to assess whether parameters of retinal and choriocapillaris perfusion are altered in patients with peripheral arterial disease (PAD). Patients with PAD and healthy controls were imaged with swept-source optical coherence tomography angiography (OCT-A). Macula centered 3 × 3 mm OCT-A scans were acquired, binarized and perfusion was evaluated for vessel density (VD) and choriocapillaris non-perfused area. Clinical examination and non-invasive assessment inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(46 reference statements)
1
8
1
Order By: Relevance
“…An impaired retinal network has been demonstrated in these systemic diseases, which may be the result of an alteration of retinal autoregulation. [3][4][5][6]17 In our study, we demonstrated a significant diminution of VD in the foveal region at CC in both 6 mm × 6 mm and 4,5 mm × 4,5 mm cubes of OCTA in the DL group. Furthermore, we observed a significant decrease of total VD in the CC in the 6 mm × 6 mm cube in patients with DL.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…An impaired retinal network has been demonstrated in these systemic diseases, which may be the result of an alteration of retinal autoregulation. [3][4][5][6]17 In our study, we demonstrated a significant diminution of VD in the foveal region at CC in both 6 mm × 6 mm and 4,5 mm × 4,5 mm cubes of OCTA in the DL group. Furthermore, we observed a significant decrease of total VD in the CC in the 6 mm × 6 mm cube in patients with DL.…”
Section: Discussionsupporting
confidence: 58%
“…An impaired retinal network has been demonstrated in these systemic diseases, which may be the result of an alteration of retinal autoregulation. 36,17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, arteriosclerosis may be associated more with retinal vessel-derived parameters or vascular disease such as retinal vein occlusion than with the other major ocular disease addressed in the present study. In a recent study, Wintergerst and colleagues reported on correlations between the ABI and the retinal and choriocapillaris vascular density as measured by optical coherence tomographic angiography [ 32 ]. Since however, we did not measure the diameters and tortuosity of the retinal vessels, we could not assess a correlation between arteriosclerosis, as measured by the ABI, and retinal vessel-derived variables.…”
Section: Discussionmentioning
confidence: 99%
“…As the underlying cause (atherosclerosis) affects all arteries in the body we theorized that vascular alterations are also present in the retinal arterial vessels. In fact, our previous work linked vascular abnormalities on ocular optical coherence tomography angiography (OCT-A) to PAD 4 . In our current work, we aim to investigate whether a similar link can be made with results from color fundus photography (CFP), a widely available and non-invasive imaging modality in which no specific findings characteristic for PAD have been described so far 5 .…”
mentioning
confidence: 99%